[No smoking ; Advancing science ; Bish [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Focuses on banning smoking in government offices and public places and campaign in support of a Congressional bill banning advertising of cigarettes. Laparoscopy, a new method of surgery that enables doctors to perform operations without "opening up" patients. Pop singer comppser Stephen Bishop in concert with Side A Band.
No smoking (15 min.) -- Advance in science (17 min.) -- Bish (15 min.)
VHS.
Keywords: Bishop, Stephen -- Interviews; Anti-smoking Movement; Smoking -- Government policy; Advertising -- Cigarettes -- Philippines; Laparoscopy